Molecular mechanism of inhibition of firefly luminescence by local anesthetics. - Ueda, I (1976)
The kinetics of the action of local anesthetics upon firefly luciferin and luciferase systems is presented. Clinical concentrations of local anesthetics inhibited this ATP-induced luminescence in a dose-dependent manner. From the effects of temperature and pH upon the inhibitory action of the local anesthetics, it is concluded that hydrophobic ligand-enzyme interaction is the predominant cause of the inhibition, but hydrophilic interaction also contributes to the inhibition to a lesser degree. A molecular theory of anesthesia is outlined which postulates that release of electrostricted water molecules from the hydrophilic parts of the enzyme due to the protein conformational changes induced by anesthetics is the cause of the decreased luminescence. A similar mechanism is expected to occur at the cell membrane, which probably dehydrates the sodium channel and suppresses the conductance of this ion across the membrane. These events lead to a volume expansion of the total system, and the system becomes reactive to a pressure which reverses the anesthesia by shifting the equilibrium to the nonanesthetized original volume. The pressure antagonism of anesthesia can be explained by this overall volume expansion and not by a mere swelling of the cell membrane.